An attempt to quantify the placebo effect from a three-week simulated altitude training camp in elite race walkers - Saunders, P. U.; Ahlgrim, C.; Vallance, B.; Green, D. J.; Robertson, E. Y.; Clark, S. A.; Schumacher, Y. O.; Gore, C. J. (International Journal of Sports Physiology and Performance, 2010)
Purpose: To quantify physiological and performance effects of hypoxic exposure, a training camp, the placebo effect, and a combination of these factors. Methods: Elite Australian and International race walkers (n = 17) were recruited, including men and women. Three groups were assigned: 1) Live High:Train Low (LHTL, n = 6) of 14 h/d at 3000 m simulated altitude; 2) Placebo (n = 6) of 14 h/d of normoxic exposure (600 m); and 3) Nocebo (n = 5) living in normoxia. All groups undertook similar training during the intervention. Physiological and performance measures included 10-min maximal treadmill distance, peak oxygen uptake (VO2peak), walking economy, and hemoglobin mass (Hbmass). Results: Blinding failed, so the Placebo group was a second control group aware of the treatment. All three groups improved treadmill performance by approx. 4%. Compared with Placebo, LHTL increased Hbmass by 8.6% (90% CI: 3.5 to 14.0%; P = .01, very likely), VO2peak by 2.7% (-2.2 to 7.9%; P = .34, possibly), but had no additional improvement in treadmill distance (-0.8%, -4.6 to 3.8%; P = .75, unlikely) or economy (-8.2%, -24.1 to 5.7%; P = .31, unlikely). Compared with Nocebo, LHTL increased Hbmass by 5.5% (2.5 to 8.7%; P = .01, very likely), VO2peak by 5.8% (2.3 to 9.4%; P = .02, very likely), but had no additional improvement in treadmill distance (0.3%, -1.9 to 2.5%; P = .75, possibly) and had a decrease in walking economy (-16.5%, -30.5 to 3.9%; P = .04, very likely). Conclusion: Overall, 3-wk LHTL simulated altitude training for 14 h/d increased Hbmass and VO2peak, but the improvement in treadmill performance was not greater than the training camp effect.